Sesquiterpene biosynthesis in a leafy liverwort Radula lindenbergiana Gottsche ex C. Hartm. (October 2021) - Fan, Honghong; Wei, Guo; Chen, Xinlu; Guo, Hong; Crandall-Stotler, Barbara; Köllner, Tobias G.; Chen, Feng
Abstract: Liverworts (Marchantiophyta) are among the earliest diverging lineages of extant land plants. Among their unique features, most liverworts contain membrane-bound oil bodies, organelles that accumulate diverse secondary metabolites, especially terpenoids. In contrast to the rich information on liverwort terpenoid chemistry, little is known about their biosynthesis. Recently, terpenoid biosynthesis was studied in a model thalloid species Marchantia polymorpha, in which sesquiterpenes and monoterpenes are biosynthesized by a new type of terpene synthases termed microbial terpene synthase-like (MTPSL) proteins. Here we study terpenoid biosynthesis in a leafy liverwort Radula lindenbergiana . Vegetative plants of R. lindenbergiana were found to contain a mixture of sesquiterpenes, with ( E, E )-α-farnesene/β-curcumene and ( Z )-β-bisabolene being the most abundant constituents. From the analysis of the R. lindenbergiana transcriptome, five full-length MTPSL genes were identified. They were designated RlMTPSL1-5, respectively. Recombinant RlMTPSL proteins were produced in Escherichia coli and tested for sesquiterpene synthase activities using farnesyl diphosphate (FPP) as substrate. All except RlMTPSL5 were demonstrated to catalyze the formation of different sesquiterpenes. RlMTPSL1 produced multiple sesquiterpenes with eremophilene and an unidentified sesquiterpene as major products. The major products of RlMTPSL2 and RlMTPSL3 were β-elemene and an unidentified sesquiterpene, respectively. RlMTPSL4 was also a multi-product sesquiterpene synthase with an unidentified sesquiterpene being the major product. Homology-based structural modeling was performed to understand the structural basis underlying different product profiles of the RlMTPSLs proteins. Most of the sesquiterpene products of the four active RlMTPSLs were also detected in R. lindenbergiana plants. Expression levels of the four RlMTPSL genes encoding active enzymes in vegetative plants were compared. In phylogenetic analysis, RlMTPSL genes were found to cluster together, indicating lineage-specific expansion of MTPSL genes in lineages leading to R. lindenbergiana and M. polymorpha . This study strengthens evidence for the contribution of MTPSL genes to terpenoid biosynthesis in liverworts. Graphical abstract: Image 1 Highlights: The leafy liverwort Radula lindenbergiana produces a mixture of sesquiterpenes. MTPSL genes were identified to be responsible for sesquiterpene biosynthesis in R. lindenbergiana . Phylogenetic analysis indicates specific-specific expansion of MTPSL genes in liverworts.